CURING OF DIGLYCIDAL ESTERS OF BISPHENOLS WITH AMINE HARDENERS (World Science, 2021)
The effect of hardeners on the properties of cured epoxy polymers is studied. For the purpose of synthesis of polymers with increased thermal properties. Theglycide esters of polycyclic bisphenols synthesized by us were used as a diol component. Since the thermal and heat resistance of polymers, in addition to the chemical structure of bisphenols, also depend on the structure of the hardener used, amine hardeners of different chemical structure are used to improve the thermal parameters of polymers, both heat resistance and heat resistance. The influence of the chemical structure of these hardeners on the properties of epoxy polymers is studied. Cured epoxy polymers are characterized by high heat resistance. High heat resistance results are obtained by 4,4′-diaminodiphenylsulfone, benzidine, 4,4′-diaminodiphenyloxide and other aromatic diamines. Polymers obtained by curing with these hardeners are deformed in the temperature range of 220-245°C. The use of the above hardeners gives high results in terms of heat resistance. In all cases, the polymers obtained on the basis of these hardeners decrease in weight by 10% in the temperature range of 340-400°C.